Research methods for reduced-impact logging: workshop results - Putz, F.E.; Elias; Sist, P.; Dykstra, D.P.; Heinrich, R. (Center for International Forestry Research, 1996)
In July 1996, with assistance from FAO, USAID, and the USDA Forest Service, CIFOR offered its first International Research Training Seminar on Reduced-Impact Timber Harvesting and Natural Forest Management. Participants were drawn from ten countries and represented disciplines ranging from silviculture and hydrology to wildlife biology. Throughout the workshop, field exercises were integrated with classroom activities, initially in the experimental forest plantation near CIFOR's headquarters, and later at an industrial timber concession in East Kalimantan. Participants also carried out a one-day research project on some aspect of forest management. Their written reports constitute the bulk of this publication and have been grouped by subject matter. The first group comprises seven papers concerned with soil compaction and erosion; the second consists of ten papers, one on tree damage and the remainder on the density or growth of trees occurring in different situations and under different conditions.